AN ANALYSIS ON STUDENTS’ SPEAKING ABILITY THROUGH STORYTELLING FOR GRADE X SENIOR HIGH SCHOOL - Khairani Nur Adha and Rahmad Husein (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2016)
The aim of this research was to find out the ability of the first year students in speaking by using storytelling at MAS. Al-Jam’iyatul Wasliyah. The design of this research was descriptive research. The population of this research was 20 students of XC class in the first grade at MAS. Al-Jam’iyatul Wasliyah. In selecting the sample the writer used random sampling technique. The total number of the sample was 12 students. The data was collected by using oral test. The researcher only measured the ability of students’ speaking in storytelling by considering five components of speaking: (grammar, vocabulary, pronunciation, fluency, and comprehension). And their speaking had been recorded by using phone recorder. From the result of analyzing the data, the researcher found that the students’ speaking ability by using storytelling was moderate. It proved by the fact that 4 students (33.33%) classified as high ability, 4 students (33.33%) classified as moderate ability, and 4 students (33.33%) classified as low ability. Based on the data, the students’ score were bigger in the high and moderate level than in the low ability level. Based on the research finding, the English teacher is suggested to consider the five components in scoring speaking ability (grammar, vocabulary, pronunciation, fluency, and comprehension). The students are suggested to do more practice in pronunciation and fluency, because they dominantly speak incorrect pronunciation and have pauses in the sentences. Students are also suggested to enrich their vocabulary by using storytelling.